INTRA ARTICULAR CALCANEAL FRACTURES: A CLINICAL AND BIOMECHANICAL ANALYSIS - Kuschnaroff Contreras, Marcos Emilio (Rev Bras Ortop, 2015)
Objective: Verify the variables of plantar pressure distribution of patients submitted to surgical procedure for calcaneal fracture, and correlate them with two different surgical approaches. Method: The authors studied 15 patients between 20 and 53 years of age (average 40.06 yrs.) who had intra-joint calcaneal fractures, submitted to surgical treatment by means of two different approaches: the lateral and the sinus tarsi. The authors checked the plantar pressure distribution by correlating these variables with the two different surgical approaches. The plantar pressure distribution was assessed using the Pedar System (Novel, Gmbh, Munich, Germany), by checking the maximum peak of the hindfoot and forefoot pressure on the affected and the normal sides. Results: the mean maximum pressure of the hindfoot plantigram in both approaches showed no statistical difference (t=0.11; p=0.91), as well as the mean maximum pressure of the forefoot plantigram (t=-0,48; p=0,64). Conclusion: The authors have concluded that there were no significant statistical differences between the average maximum peak of the hindfoot and forefoot pressure on the affected side as compared to the normal side, and these variables have showed no differences when compared to the surgical approach used.